Contribution to the aphaenopsian trechine beetle from Nanling region, South China (Coleoptera: Carabidae: Trechini) - Li, Ran; Liu, Zi-Jun; Huang, Sun-Bin (Zootaxa, 2024)
Despite previous reports of several aphaenopsian trechine genera from various regions of South China, Guilin has remained unrecorded until now. This study lists the first report of an aphaenopsian trechine Yinaphaenops guilinensis gen. nov., sp. nov. from Guilin, expanding the known diversity of this group in Nanling region. Additionally, the male of Sinaphaenopoides zhaoyiae Tian, Huang & Jia, 2023 is reported and described for the first time.